2019
DOI: 10.21203/rs.2.19610/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Factors Influencing Obstetric Home Delivery and Outcome Among Women of Reproductive Age in Dusmareb District, Somalia

Abstract: Background: Homebirth (home delivery) is a birth that takes place in a residence rather than in a hospital or a birth center. Aims: The aim of the study is to determine factors influencing obstetric home delivery and the outcomes among women of reproductive age in Dusmareb district, Somalia. Methods: The study was used a descriptive cross-sectional study in Dusamreb district of Somalia with both qualitative and quantitative techniques of data collections and random technique was used to select 228 women of rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…Similar conclusions were reached to those of Jama et al 10 Their research revealed that 41% of respondents had at least one home birth. In their study, respondents had a mean age of 32.98.1 years; those with 7-9 children were nearly 2.5 times more likely to have a home delivery (OR=2.38, p=0.056).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Similar conclusions were reached to those of Jama et al 10 Their research revealed that 41% of respondents had at least one home birth. In their study, respondents had a mean age of 32.98.1 years; those with 7-9 children were nearly 2.5 times more likely to have a home delivery (OR=2.38, p=0.056).…”
Section: Discussionsupporting
confidence: 89%
“…13 The majority of respondents in this research (77.2%) had a favorable opinion of health facility staff, however they did not specify why they preferred to give birth at home. In accordance, Jama et al 10 discovered that 141 (61.8%) women made their own decision regarding where they delivered their kid, 50 (22.0%) claimed that their husbands made the decision, and 37 (16%) reported that their mother made the decision. These findings were consistent with those of the Namibia Demographic Health Survey (NDHSS) (2015).…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Gender disparities in mental health are widely recognized, with women disproportionately affected by various mental disorders. Apart from specific conditions like PMDD, PMS, and postpartum depression, women are at greater risk than men for developing anxiety, depression, somatoform and eating disorders, as well as experiencing suicide attempts [7][8][9]. Polygamy is a form of marriage that involves having numerous spouses [10].…”
Section: Introductionmentioning
confidence: 99%